2023
DOI: 10.1111/den.14539
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of esketamine in propofol based sedation for endoscopic variceal ligation with or without injection sclerotherapy: Randomized controlled trial

Abstract: ObjectivesEsketamine is an S (+) enantiomer of ketamine with greater potency and similar psychomimetic effects compared to racemic ketamine. We aimed to explore the safety of esketamine in different doses as an adjuvant to propofol in patients undergoing endoscopic variceal ligation (EVL) with or without injection sclerotherapy.MethodsOne hundred patients were randomized to receive sedation with propofol 1.5 mg/kg in combination with sufentanil 0.1 μg/kg (group S), esketamine 0.2 mg/kg (group E0.2), esketamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…[14,15] Previous studies observed that this effect of esketamine can be used to improve hemodynamic stability in patients undergoing procedures under general anesthesia. [15][16][17][18][19][20][21][22] In light of the evidence from previous studies, we hypothesize that esketamine may improve blood pressure during the induction phase of the procedure since it stimulates the sympathetic nervous system, making it an ideal drug for the induction of anesthesia in unstable patients. [23,24]…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] Previous studies observed that this effect of esketamine can be used to improve hemodynamic stability in patients undergoing procedures under general anesthesia. [15][16][17][18][19][20][21][22] In light of the evidence from previous studies, we hypothesize that esketamine may improve blood pressure during the induction phase of the procedure since it stimulates the sympathetic nervous system, making it an ideal drug for the induction of anesthesia in unstable patients. [23,24]…”
Section: Introductionmentioning
confidence: 99%
“…One promising alternative is esketamine, an N -methyl- d -aspartate receptor antagonist and the dextrorotatory isomer of ketamine. Esketamine possesses twice the potency of ketamine in terms of hypnotic and analgesic effects, with fewer psychiatric adverse effects . Previous studies have also indicated that a subanesthetic dose of esketamine can maintain hemodynamic stability and reduce respiratory depression in surgical patients .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on new analgesics such as sufentanil and esketamine in gastrointestinal endoscopy have been conducted mainly in China. 1,8,9 However, it is not known which analgesics can be added to propofol to reduce adverse events, such as hypotension. In this issue of Digestive Endoscopy, Chen et al 1 investigated the efficacy and safety of propofol plus esketamine sedation compared with sufentanil during endoscopic variceal ligation (EVL) with or without injection sclerotherapy in patients with liver cirrhosis.…”
mentioning
confidence: 99%
“…A balance between efficacy and safety is important. Chen et al 1 . investigated the efficacy and safety of sedation during esophageal endoscopy in patients with liver cirrhosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation